Computational and Experimental Evaluation of Alkaloid Compounds from Papaver somniferum as Dual COX-2 and TNF-α Inhibitors - Poyizar Poyizar; Nurfitriyana Rahmat; Syaiful Katadi; Rahayu Aprianti; Irman Idrus (Newinera Publisher, 2026)
This study aimed to evaluate the computational and experimental potential of alkaloid compounds isolated from Papaver somniferum as dual inhibitors of cyclooxygenase-2 (COX-2) and tumor necrosis factor-alpha (TNF-α) in an in vitro inflammatory model. The alkaloid fraction was purified from dried capsules/latex of Papaver somniferum and subsequently tested using lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophage cells. Anti-inflammatory activity was assessed by measuring reductions in prostaglandin E₂ (PGE₂) production as an indicator of COX-2 inhibition and TNF-α levels in the cell culture supernatant. Preliminary safety evaluation was conducted using an MTT cytotoxicity assay on non-tumor cells, along with analysis of COX-2 and TNF-α gene expression using RT-qPCR. The alkaloid fraction exhibited concentration-dependent inhibitory effects on both PGE₂ and TNF-α production, with IC₅₀ values observed within the intermediate concentration range. In contrast, the CC₅₀ value in non-tumor cells was substantially higher, resulting in a favorable selectivity index that suggests a relatively wide therapeutic window. Furthermore, treatment with non-toxic concentrations of the alkaloid fraction led to a significant downregulation of COX-2 and TNF-α mRNA expression, supporting the hypothesis that its anti-inflammatory mechanism involves modulation of pro-inflammatory transcriptional pathways. Overall, the alkaloid fraction derived from Papaver somniferum demonstrates promising potential as a multitarget anti-inflammatory agent and warrants further investigation as a source of lead compounds or phytopharmaceutical candidates for the treatment of chronic inflammatory diseases.